Role of transporters in the distribution of platinum-based drugs - Harrach, Saliha; Ciarimboli, Giuliano (Frontiers in Pharmacology, 2015)
Platinum derivatives used as chemotherapeutic drugs such as cisplatin and oxaliplatin have a potent antitumor activity. However, severe side effects such as nephro-, oto-, and neurotoxicity are associated with their use. Effects and side effects of platinum-based drugs are in part caused by their transporter-mediated uptake in target and non target cells. In this mini review, the transport systems involved in cellular handling of platinum derivatives are illustrated, focusing on transporters for cisplatin. The copper transporter 1 seems to be of particular importance for cisplatin uptake in tumor cells, while the organic cation transporter (OCT) 2, due to its specific organ distribution, may play a major role in the development of undesired cisplatin side effects. In polarized cells, e.g. in renal proximal tubule cells, apically expressed transporters, such as multidrug and toxin extrusion protein 1, mediate secretion of cisplatin and in this way contribute to the control of its toxic effects. Specific inhibition of cisplatin uptake transporters such as the OCTs may be an attractive therapeutic option to reduce its toxicity, without impairing its antitumor efficacy.